**Dan Banks**answered

To solve the equation 4x + 3 = 2x + 11 first the like terms need to be collected so we can isolate the x value and thus find x. To do this, arrange the x terms on one side of the equation and the integers on the other. When performing this action, remember that when a term crosses the equals sign it changes from positive to negative and vice versa.

Find x by collecting like terms.

4x + 3 = 2x + 11

Shift the 2x across the equals sign to collect like terms, it become -2x. Likewise with the 3, thus it becomes - 3. Now we have all the x terms on one side and the integers on the other. This leaves us with...

4x - 2x = 11 - 3

Then simplify by subtracting the 2x from the 4x to leave 2x, and subtract the 3 from 11 to get 8. Therefore...

2x = 8

Now we can divide both terms by 2 to get a value for x.

x = 4

To check the answer substitute the x value back into the equation, which leaves us with...

4(4) + 3 = 2(4) + 11

16 + 3 = 8 + 11

19 = 19 therefore 4 is the correct value for x.